The study of the reaction of morpholine with aryl halide and aliphatic halide - Dorairaaj, A/L Sivasubramaniam (Universiti Malaysia Sarawak, UNIMAS, 2013)
This study was aimed to synthesized the morpholine derivatives by the cross coupling reaction between morpholine and an aryl halide. The reaction of morpholine with 4-bromobenzaldhyde and 4-bromoanisole. When morpholine reacted with 4-bromoanisole, the reaction was failed but morpholine reacted with 4-bromobenzaldehyde produced 4-morpholine-4-yl-benzaldehyde, which showed that the reaction was successful. The reaction of morpholine with 4-bromobenzaldehyde was compared in the presence and absence of the copper(I) iodide which act as a catalyst. The GC result showed that the conversion of the product without catalyst was much more higher than the reaction with catalyst under the same condition. The side product also was discovered in the reaction without catalyst, the morpholine actually was attacked to the carbon in the carbonyl group of 4-bromobenzaldehyde to produce 4-bromobenzoic acid,morpholide.